Beca 6000 in Andalusia: policy, discourse and practices - Jiménez, Magdalena; Luzón, Antonio; Torres, Mónica (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
This paper analyzes the 6000 Grant programme introduced in Andalusia in the 2009-2010 academic year with the aim of reducing early educational dropout, focusing on students from very low income families enrolled in post-obligatory non-university courses. The research undertakes a descriptive analysis using the data provided by the General Directorate of Participation and Equity of the Junta de Andalucía, regarding the evolution of the number of beneficiaries, the coverage rate, distribution by gender, and the effects on performance. Furthermore, on the basis of the analysis of the legislative texts, we discuss questions concerning the definition of the beneficiaries, the requirements for retaining the grant, and the monitoring strategies contained in the institutional design of the programme. Finally, we analyze the impacts and limitations of the programme from the recipients’ viewpoint.